Concise thermodynamics : principles and applications in physical science and engineering - Dunning-Davies, J., 1941- (Horwood, 2007)
This one-semester course text introduces basic principles of thermodynamics and considers a variety of applications in science and engineering. The modern coverage is compact yet self-contained and holistic, with adequate material in a concise and economically-priced book for advanced undergraduates and postgraduates reading for first and higher degrees, and for professionals in research and industry. The mathematical prerequisite is an understanding of partial differentiation. Introduces basic principles of thermodynamics and considers a variety of applications in science and engineeringThe modern coverage is compact yet self-contained and holistic, with adequate and concise material.